Long-term effects of secukinumab on MRI findings in relation to clinical efficacy in subjects with active ankylosing spondylitis: an observational study. Issue 2 (6th August 2015) - Baraliakos, Xenofon; Borah, Babul; Braun, Juergen; Baeten, Dominique; Laurent, Didier; Sieper, Joachim; Emery, Paul; McInnes, Iain B; van Laar, Jacob M; Wordsworth, Paul; Wollenhaupt, Juergen; Kellner, Herbert; et al.
Abstract : Introduction: A 28-week study suggested efficacy of the anti-interleukin-17A monoclonal antibody secukinumab in active ankylosing spondylitis (AS). MRI-assessed inflammation was reduced at weeks 6, 28. Objective: To analyse the longer-term effects of secukinumab on MRI inflammatory and non-inflammatory spinal lesions in relation to its clinical efficacy in subjects with active AS. Methods: Spinal MRI results (baseline, week 94) for 13 subjects with AS initially treated with secukinumab 2×10 mg/kg intravenously (n=10) or placebo (n=3) and receiving a secukinumab maintenance dose of 3 mg/kg IV every 4 weeks up to week 94 were evaluated by the Berlin score; inflammatory/non-inflammatory (fatty) changes were assessed at vertebral edges (VEs). Results were compared with clinical outcomes. Results: Most of the 13 subjects assessed at week 94 had sustained clinical responses: 8 (62%) achieved Assessment of SpondyloArthritis international Society 20% (ASAS20), including 6 (46%) achieving ASAS40 responses, corresponding to 75% and 83% reductions in the Berlin score, respectively. In the 10 subjects treated with secukinumab throughout the study period, 79/91 (87%) inflammatory VEs at baseline resolved by week 94; new fatty lesions occurred in 39/796 (4.9%) of VEs; 87/124 (70%) VEs with fatty lesions at baseline remained unchanged; 30% were no longer visible. Conclusions: In this pilot study, secukinumab treatment up to 2 years yielded sustained clinical improvement accompanied by regression of spinal inflammation. The impact of secukinumab on the development of fatty changes and bone formation in AS will be assessed in larger trials. Trial registration number: This study is registered with ClinicalTrials.gov, number NCT00809159 .